LONG WAVELENGTH GRAVITY AND TOPOGRAPHY ANOMALIES - Watts, A; Daly, S (Annual Reviews Inc., 1981)
This reviews the current knowledge of gravity and topography anomalies on the Earth which are of large horizontal extent. It emphasises gravity and topography anomalies characterised by wavelengths in the range of a few hundred to a few thousand km since these anomalies appear to hold the most promise in determing information on the plan form of convection in the mantle. We limit the review to mainly oceanic regions. -from Authors